Perception of Key Ethical Issues in Assisted Reproductive Technology (ART) by Providers and Clients in Nigeria - Ezeome IV; Akintola SO; Jegede AS; Ezeome ER (Dove Medical Press, 2021)
Ijeoma V Ezeome,1,2 Simisola O Akintola,2,3 Ayodele S Jegede,2,4 Emmanuel R Ezeome5 1Department of Obstetrics & Gynecology, Faculty of Medical Sciences, College of Medicine, University of Nigeria, Enugu, Nigeria; 2Department of Bioethics, Faculty of Multidisciplinary Studies and Faculty of Clinical Sciences, University of Ibadan, Ibadan, Nigeria; 3Department of Business and Private Law, Faculty of Law, University of Ibadan, Ibadan, Oyo State, Nigeria; 4Department of Sociology, Faculty of the Social Sciences, University of Ibadan, Ibadan, Oyo State, Nigeria; 5Department of Surgery, Faculty of Medical Sciences, College of Medicine, University of Nigeria, Enugu, NigeriaCorrespondence: Ijeoma V EzeomeDepartment of Obstetrics & Gynaecology, Faculty of Medical Sciences, College of Medicine, University of Nigeria, Ituku-Ozalla Campus, Enugu, NigeriaTel +234 805 812 4721Email ezeomeij@gmail.com; ijeoma.ezeome@unn.edu.ngPurpose: In the past decade, developments in the field of Assisted Reproductive Technology (ART) have intensified the hopes and the desires of infertile people to overcome infertility, resulting in an increasing demand for such services worldwide. However, as developments in ART have evolved rapidly, so have ethical, social, and political controversies surrounding many aspects arisen. It is known that societal ethics is dependent on the values and culture of a given group. We sought to explore how practitioners and clients in Nigeria perceive some Key ethical issues surrounding ART.Materials and Methods: This was an explorative descriptive study involving in-depth interview of three ART providers and eight female ART clients, all domiciled in Southeastern Nigeria. Sampling was by purposive and snowballing techniques for providers and clients, respectively. Ethical approval was obtained from University of Ibadan/University College Hospital and University of Nigeria Teaching Hospital Research Ethics Committees. Responses were grouped into themes for ease of discussion.Results: Providers and clients were in support of sex selection for family balancing, and multiple embryo transfers. They also perceive that the health of the woman should be the factor considered and not biological age for service provision. However, views differed on marital status as an access factor. Participants were in support of legally binding regulations to guide practice.Conclusion: A culturally sensitive national regulation is recommended to guide practice in this vital area of reproduction.Keywords: new conception methods, societal ethics, national regulation, practitioners, patients